TPACK VENN DIAGRAM: MEASURING THE BALANCE OF IMPLEMENTATION OF LEARNING MODELS IN ENTERING THE INDUSTRY 4.0 ERA (STUDY ON GEOGRAPHY LEARNING IN 2013 CURRICULUM) - Yani, Ahmad; Ruhimat, Mamat; Mulyadi, Asep (Universitas Pendidikan Indonesia, 2019)
This study tries to make a visualization of the three components of TPACK (Technological Pedagogical Content Knowledge) mastery in the form of a venn diagram. The research method used is descriptive with survey technique. The instruments used were questionnaires and interviews. The location of the questionnaire study consisted of West Java Province, Bengkulu Province, and other provinces that were filled out online through Google forms. Subjects were geography teachers with 121 respondents. Data obtained through questionnaires were analyzed in a quantitative manner while interview data were carried out qualitatively. The results of the study can make a hypothetical form of TPACK venn diagrams to illustrate the TPACK mastery profile of geography teachers, namely the slices price of TPACK (25%), PCK (75%), TCK (35%), and TPK (15%). The implication of obtaining the data is that policy makers can improve the competence of geography teachers starting from training on TCK and TPK.